Sustainable mobility and electric vehicle adoption: a study on the impact of perceived benefits and risks - Yildiz, Bülent; Çiğdem, Şemsettin; Meidutė-Kavaliauskienė, Ieva (Transport, 2024)
The shift towards sustainable transportation is becoming increasingly important as the negative impact of traditional fuel-powered vehicles on the environment becomes more evident. Electric Vehicles (EVs) are considered a viable solution to this problem, and understanding the factors that influence consumer intention to purchase EVs is crucial for their widespread adoption. This study investigates the factors that influence individuals’ intention to purchase EVs. 4 independent variables were considered: Perceived Environmental Benefit (PEB), Perceived Performance Benefit (PPB), Perceived Performance Risk (PPR), and Perceived Financial Risk (PFR). A survey was conducted with 398 respondents, and the data collected were analysed using Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM). The results indicate that PEB, PPB, PPR, and PFR have significant effects on Purchase Intention (PI). Specifically, PEB and PPB positively affect PI, while PPR and PFR negatively affect it. These findings suggest that improving the PEBs and PPBs of EVs and reducing perceived performance and financial risks could encourage more individuals to purchase them.